The Role Of Regulatory Credibility In Effective Bank Regulation (International Journal of Scientific Research and Management (IJSRM), 2016)
Regulatory credibility is an important framework for effective bank regulation in any financial system. It stimulates not only efficient roadmap for banking industry regulation but for effective supervision. The study contributes to the existing literature by investigating the role of regulatory credibility in effective bank regulation in Nigeria using ex post facto research design to ascertain the direction of causation between assets quality of banks, capital adequacy of banks and liquidity of banks in Nigeria from 2005 to 2010. The results from the Granger casualty test depicts that there is no direction of causation between assets quality of banks, capital adequacy of banks and liquidity of banks in Nigeria within the period under review while the direction of causation between capital adequacy and liquidity is unidirectional within the period under review. Base on the findings, the researcher recommends that regulatory authority should often review their regulatory and supervisory framework to ensure that its policy is always in tandem with international best practices to reduce insider abuse especially in the area of credit risk, market risk and operating risk to mitigate the banking menace of high incidence of nonperforming loans by boosting their assets quality. Banks minimum capital base should be reviewed often at least twice per decade, this will enhance their capital adequacy and reduce the over dependence of the banking sector on the customer’s deposits in Nigeria